2021
DOI: 10.1111/iwj.13703
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of craniofacial necrotising fasciitis: Analysis of clinical risk factors

Abstract: Necrotising fasciitis (NF) is a rapidly progressing fatal disease. Craniofacial necrotising fasciitis (CNF) is limited to the region above the mandibular margin, and early diagnosis is particularly difficult in the absence of related studies. Ten‐year data of patients with craniofacial infection were collected from four separate hospitals. Based on the diagnostic criteria, patients were classified into abscess and CNF. The risk factors for early diagnosis were analysed by comparing the two groups. Simple absce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…We calculated the diagnostic accuracy (i.e., diagnostic odds ratio [DOR]) and created a summary receiver operating characteristic (SROC) curve to calculate the area under the curve (AUC). 3,5,9,14,15,[18][19][20][21] The DORs were calculated as (true positives  true negatives)/(false positives  false negatives), with 95% confidence intervals (CIs) using a random effect model taking into account both intrastudy and interstudy variations. DORs range from 0 to infinity, with high values indicating better diagnostic performance, and a value of 1 indicating that the presence of disease cannot be inferred.…”
Section: Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
“…We calculated the diagnostic accuracy (i.e., diagnostic odds ratio [DOR]) and created a summary receiver operating characteristic (SROC) curve to calculate the area under the curve (AUC). 3,5,9,14,15,[18][19][20][21] The DORs were calculated as (true positives  true negatives)/(false positives  false negatives), with 95% confidence intervals (CIs) using a random effect model taking into account both intrastudy and interstudy variations. DORs range from 0 to infinity, with high values indicating better diagnostic performance, and a value of 1 indicating that the presence of disease cannot be inferred.…”
Section: Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Age in older than 60 year or younger than 1 year are at a high risk of mortalities. Our patient age is 65 years old 17,18 .…”
Section: Figure 4 Wound Condition After Skin Grafting Discussionmentioning
confidence: 96%
“…The LRINEC score has been proven useful for detecting severe infections of the upper and lower extremities, which has improved the efficiency of the early diagnosis[ 13 ]. Some reports have shown that lower albumin levels in patients are associated with a more fatal prognosis[ 9 , 14 ]. Procalcitonin is synthesized in various tissues and organs in response to bacterial, fungal, and parasitic infections, and it has become a useful marker for determining whether antibiotics should be used for the duration of treatment[ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of hospitalization, the glycated hemoglobin (HbA1C) level was elevated at 17.1, indicating uncontrolled diabetes. The Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) scoring system was used for proper diagnosis of necrotizing fasciitis[ 9 ]. Laboratory findings showed a high white blood cell (WBC) count (15170/μL; LRINEC score 1 point), a low hemoglobin level (10.5 g/dL; LRINEC score 2 points), an elevated high-sensitivity C-reactive protein (hs-CRP) level (212.94 mg/L; LRINEC score 4 points), a high glucose level (242 mg/dL; LRINEC score 1 point), and a slightly low sodium level (134 mmol/L; LRINEC score 2 points).…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation